Perbandingan Makna Ekaristi dalam Gereja Katolik dan HKBP: Suatu Kajian Roti dan Anggur Berdasarkan Praktik Liturgi - Casandro Siregar; Daniel Pasaribu; Hizkia Pasaribu; Jenita Lumbantoruan; Ribka Nainggolan (Green Publisher Indonesia, 2026)
This study examines the comparative meaning of the Eucharist in the Catholic Church and the Batak Protestant Christian Church (HKBP), focusing on the symbols of bread and wine in the liturgical practices of both traditions. Through a theological-liturgical approach and comparative analysis, it highlights how the two churches' understanding of the Eucharist developed from a biblical basis, ecclesiastical tradition, and their respective historical contexts. In the Catholic Church, bread and wine are understood as the body and blood of Christ made real through transubstantiation, making the Eucharistic liturgy the pinnacle and source of the life of faith. Meanwhile, in the HKBP, bread and wine are interpreted as signs and means of communion with Christ within a Reformed-Lutheran theological framework with an emphasis on grace, remembrance, and the faithfulness of the people. This comparison shows that although both churches use the same symbols, their theological meanings, liturgical forms, and understanding of Christ's presence in the Eucharist have different yet mutually enriching characteristics. This study contributes to ecumenical dialogue and the development of sacramental understanding across traditions.